Two's a Crowd - Katschke, Judy; Series Created by Griffard, Robert and Adler, Howard (London HarperCollinsEntertainment, 2002)
Meet Mary-Kate and Ashley, the Tween Queen Twins! Your new best friends have just arrived...
Keywords: Friendship -- Twins